Influence of bone loss and inclination of incisor on periradicular stresses due to simulated bite force - Samuel RODRIGUES; José Roberto CORTELLI; Ana Paula Rosifini Alves CLARO; Rosana Villela CHAGAS; Lais Regiane da Silva CONCÍLIO; Luciana Paula Benicio ARCAS; Cristiane Aparecida de Assis CLARO
Abstract Introduction Adults with sequelae of periodontal disease tend to have bone loss, with consequent flaring of the maxillary incisors. Objective The influence of bone loss and the inclination of the maxillary incisor in the distribution of stresses due to simulated bite forces was studied. Material and method Models in epoxy resin were made in three conditions (without bone loss and with bone loss of 5mm and 8mm). Increases in the labial inclination of the maxillary incisor of 10° and 20° were obtained with a beveled metallic block. Loads of 100N were applied five times in each condition using a universal test machine. The models were observed and filmed with a circular polariscope. Orders of isochromatic fringes (stresses) on the labial, lingual, and apex surfaces were recorded. The agreement of the data was evaluated using the weighted kappa test, and the results were 0.89 and 0.82 for intra- and inter-examiners, respectively. Result The results of the Kruskal-Wallis and SNK tests indicated higher stresses (2.0) with increased labial inclination in the labial surface; higher stresses (2.67) with increased bone loss; higher greater stresses with the association of bone loss and labial-inclination (3.6); and the highest stresses tended to concentrate on the labial surfaces, except in cases of normal inclination and without bone loss (0.45). Conclusion It was concluded that increases in both the labial inclination of the maxillary incisors and bone loss increase periradicular stresses, and the combination of these factors further increases the stresses due to bite forces, with the highest concentration on the labial side.